2020
DOI: 10.1167/iovs.61.2.15
|View full text |Cite
|
Sign up to set email alerts
|

Patchy Scotoma Observed in Chorioretinal Patchy Atrophy of Myopic Macular Degeneration

Abstract: PURPOSE. To investigate the retinal sensitivity of highly myopic eyes with chorioretinal patchy atrophy (PA) using microperimetry. METHODS. Fifty-two eyes of 32 patients with high myopia were prospectively included. Twenty-two eyes of 16 patients had PA lesions; eyes without PA were analyzed as controls. Testing points on microperimetry in eyes with PA were designated as 3 zones: zone 1 as the PA lesion including its borders; zone 2 including testing points adjoining PA; zone 3 including all other testing poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…However, it is uncommon for extrafoveal patchy atrophy to later involve the central fovea. This means that it is rare for patchy atrophy to cause the central vision loss although this lesion leads to a paracentral absolute scotoma 123 owing to a loss of photoreceptors within the atrophic area ( Table 3 ).…”
Section: Clinical Aspects Of Pathologic Myopiamentioning
confidence: 99%
“…However, it is uncommon for extrafoveal patchy atrophy to later involve the central fovea. This means that it is rare for patchy atrophy to cause the central vision loss although this lesion leads to a paracentral absolute scotoma 123 owing to a loss of photoreceptors within the atrophic area ( Table 3 ).…”
Section: Clinical Aspects Of Pathologic Myopiamentioning
confidence: 99%
“…This finding was in concordance with Lo et al's study, in which they reported reduced retinal sensitivity in regions beyond the atrophic lesions. 23 Another key finding was that MS decreased significantly with reduced deep retinal PD (b = 0.15, P = 0.004) but not with superficial PD (b = 0.03, P = 0.62), suggesting that sparser DCP may be related to functional impairment in MMD. This finding is in line with Tsui et al's observation that DCP was associated with MS in the temporal and nasal sectors in HM but not SVP.…”
Section: Discussionmentioning
confidence: 92%
“…This finding was in concordance with Lo et al's study, in which they reported reduced retinal sensitivity in regions beyond the atrophic lesions. 23…”
Section: Discussionmentioning
confidence: 99%
“…In eyes with PA lesions (namely, category 3 myopic maculopathy), the mean retinal sensitivity was lowest at zone 1 testing points, which were within or at the border of the PA lesion, followed by the adjacent points of zone 2 and distant points of zone 3, suggesting a gradual change in retinal sensitivity across the junctional zone of the PA lesion. These results imply that microperimetry is a useful functional assay to assess altered retinal function in patients with myopic maculopathy, particularly to detect scotoma and subtle functional decline around the atrophic lesion in patients with PA. 17 The completeness of hyperreflective lines of the RPE and photoreceptors in OCT also decreased gradually across the margin of PA lesions, reflecting the differences in retinal sensitivity among the zones. Thus, it could be concluded that anatomical and functional alterations also involve the adjacent region of the PA lesion, which significantly influences retinal sensitivity.…”
Section: Discussionmentioning
confidence: 97%